4-(Dimethylamino)pyridinium tetrachloridoferrate(III) - Khadri, Amina (International Union of Crystallography, 2013)
The title salt, (C(7)H(11)N(2))[FeCl(4)], consists of one essentially planar (the r.m.s. deviation for all non-H atoms being 0.004 Å) 4-(dimethylamino)pyridinium cation and a tetrahedral tetrachloridoferrate(III) anion. The cations and anions are arranged in layers parallel to (010). Besides electrostatic interactions, the crystal packing features N—H⋯Cl and C—H⋯Cl hydrogen bonds between cations and anions, forming a three-dimensional network.